Analisis Faktor Pendukung dan Faktor Penghambat Digitalisasi Kota Palembang Menuju Smart City - Hasanah, Ade Uswatun; Lestari, Delfiazi Puji; Sari, Feni Huspita; Utami, Ida; Isabella, Isabella; Annisa, Annisa (PANDITA: Interdisciplinary Journal of Public Affairs, 2025)
Digitalization is one of the main pillars in the development of a modern city. Palembang City, as one of the big cities in Indonesia, has started its journey towards implementing the Smart City concept. The main objective of this study is to determine the efforts that have been made by the government in the development of digitalization in Palembang City by identifying supporting and inhibiting factors that influence the success of the digitalization program, as well as formulating policy recommendations to increase the effectiveness of digitalization development in the future. This study uses a qualitative approach with a descriptive-analytical method. Data were collected through in-depth interviews with stakeholders, policy document analysis, and literature studies. Research informants include city government officials, namely the Palembang City Communication and Information Office and academics as well as lecturers and the community of digital service users in free access places. In addition, secondary data were obtained from official government reports, journal articles, and current news relevant to the digitalization program in Palembang. There are 6 dimensions in the concept of a smart city according to Griffinger et al. (2007:10-14), namely, smart environment, smart mobility, smart government, smart economy, smart people, and smart living. all of these concepts are interrelated with each other. The results of the study show that digitalization increases the efficiency of public services, transparency, and community participation. However, there are challenges such as the digital divide and low technological literacy in some groups of society.